Entwining polymer chains enables strong, flexible, and super-transparent radiative coolers with low environmental impacts for foldable photovoltaics - Xinyi Tian; Feiyang Xie; Yurong Pan; Yunjie Yang; Chengling Wang; Xuanhao Zhuo; Qianyi Yao; Chenyang Cai; Changlei Xia (Chemical Engineering Journal, 2026)

Structure-evolving bioadhesive for temporally programmed osteoimmune modulation in osteoporotic bone regeneration - Qingda Li; Yurong Chen; Yining Gong; Yuan He; Bin Zhu; Senyu Xue; Luyao Feng; Yiming Ren; Xiaoyu Wu; Lu Dang; Bo Zhang; Dali He; et al. (Chemical Engineering Journal, 2026)

Influence of converting forestland to tea plantation on soil water deficit and controlling factors in subtropical hilly areas - Qian Yang; Yurong Han (CATENA, 2026)

Advancing hyperspectral nutrient modeling through transfer learning: Insights from foliar N–P–K estimation in cranberries - Dongheng Yang; Yurong Huang; Nanfeng Liu; Erin Wagner Hokanson; Nicole Hansen; Philip A. Townsend (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Dual-catalytic effects of CoN4 sites: Suppressing shuttle effect and boosting four-electron transfer in ZnI2 batteries - Le Yang; Yurong You; Weihang Feng; Jingyuan Qiao; Ye Chen; Chengdong Zhao; Wei He; Xuelian Wu; ZhengMing Sun (Chemical Engineering Journal, 2026)

The fracture mechanism of cotton stalks through FDEM analysis - Xirui Yang; Peiyu Chen; Yongcheng Zhang; Yong Zeng; Haipeng Lan; Yurong Tang (Biosystems Engineering, 2026)

Pyrethrin II impairs mitochondrial potential through ROS and MAPK pathways in HT‑22 cells - Jiaojiao Gao; Xinbi Zhang; Qie Mu; Yurong Liu; Hong Yang; Rui Cao; Xiuwei Wang; Baofeng Yu; Li Zhang; Yaoyao Guo (NeuroToxicology, 2026)

Microbial ecology and flavor formation mechanisms of high-temperature Daqu in the Huang-Huai River basin and adjacent regions: A comparative study from eastern Henan, Jiaodong peninsula, and southern Anhui - Zhendong Zhang; Kai Zhang; Qiangchuan Hou; Chengcong Yang; Zhuang Guo; Yongbo Li; Chan Wang; Yurong Wang (Food Research International, 2026)

TiO2-x/WO3-x heterostructure memristor integrating self-powered photodetection and optoelectronic synaptic functions for spectrally responsive neuromorphic vision - Yonghui Lin; Chaoyang Hu; Lu Wang; Lun Zhong; Zhuohua Liu; Yurong Liu; Ruohe Yao; Yang Li; Kuiwei Geng (Chemical Engineering Journal, 2026)

3-Monochloro-1,2-propanediol disrupts ovarian germline stem cell maintenance via Golgi stress-induced autophagy in Drosophila - Zongzhong Liu; Yurong Song; Binbin Xie; Pengpeng Xia; Junlin Yang; Jiazuo Zhu; Hua Wang; Tian Wei (Chemico-Biological Interactions, 2026)

A novel particle swarm optimizer with failure-aware searching framework for neural mass model inversion - Han Li; Yang Zou; Jiyu Tan; Zihao Jia; Yurong Li; Nianyin Zeng (Swarm and Evolutionary Computation, 2026)

Carbon emission reduction benefits analysis of recycled aggregate-based sandwich permeable bricks based on sponge effect enhancement design - Tongyuan Ni; Lihua Shen; Chenhao Yu; Haoxiang Sheng; Chengqi Yang; Yurong Zhang; Deyu Kong (Journal of Cleaner Production, 2026)

From passive to bioactive: Engineering a smart Band-Aid for complex wound care - Bin Zhu; Xueling Yang; Haiting Ren; Sergio Martin- Saldaña; Wanglin Duan; Bo Zhang; Qingzu Liu; Luyao Feng; Ye Zhu; Yurong Chen; Lu Dang; Jinqing Li; et al. (Chemical Engineering Journal, 2026)

Multiple macroeconomic benefits from mixed coastal flooding adaptation in China's coastal cities - Jiaju Lin; Shuyu Yang; Shuo Wang; Yuning Zhao; Yanhong Lin; Xiongzhi Xue; Yurong Ouyang (Ocean & Coastal Management, 2026)

Inequality in distribution of atmospheric particulate matters and their health exposure risk in Beijing-Tianjin-Hebei, China - Linan Guo; Yuehan Wang; Yi Yang; Yurong Zheng; Li Zhou; Wenbin Sun (Atmospheric Pollution Research, 2026)

Microcystin-LR-induced phosphorylation imbalance and organelle stress: An integrative review of autophagy dysregulation and cross-species toxicity - Zhuoran Teng; Asif Shahzad; Zhe Xu; Jiaojiao Xia; Jinshan Zhang; Yueli Ni; Wenjing Liu; Kun Cui; Yongping Li; Yurong Dong; Ziyuan Bai; Peng Zhang; et al. (Journal of Hazardous Materials, 2026)

Novel antioxidant peptides identified from wheat germ protein: Structure-activity relationships, stability, and cytoprotective ability - Ling Fan; Xiaolin Yang; Sen Ma; Xinrui Zhang; Jihong Huang; Jin Liu; Yurong Xing; Jingjing Cheng (Food Chemistry, 2026)

Per- and polyfluoroalkyl substances in poultry eggs in Shandong, China: Occurrence, characteristics, and risk assessment - Yurong Liu; Yanni Jiao; Xiaofei Ren; Lin Wang; Xiaolin Wang; Fengjia Zheng; Fangfang Chen; Luping Yang (Food Control, 2026)

Effects of grassland enclosure on phosphorus bioavailability and microbial nutrient limitations in the karst region of southwest China - Wangjun Li; Xiaolong Bai; Shun Zou; Bin He; Yurong Yang (European Journal of Soil Biology, 2026)

Differential nutrient resorption strategies of soybean organs for adapting to climate warming - Mengya Chen; Pingting Guan; Wei Wang; Liang Chang; Ruslan Saifutdinov; Yurong Yang; Donghui Wu (Plant and Soil, 2026)

Poly- and perfluoroalkyl substances (PFAS) in marine and freshwater fish muscle tissue from Shandong Province and implications for human exposure - Xiaolin Wang; Yurong Liu; Lijun Shao; Yanni Jiao; Lijun Zhu; Jiacheng Zhang; Lin Wang; Xiaofei Ren; Yanwen liu; Luping Yang (Marine Pollution Bulletin, 2026)

The role of DNA methylation in alcohol-mediated neurodevelopmental toxicity - Jing Gao; Bingchun Liu; Hong Chen; Peixin Xu; Xin Guo; Dongmei Yao; Xin Li; Tong Wang; Yurong Wang; Hongrui Yao; Shuwei Qiao; Jianlong Yuan; et al. (Toxicology, 2026)

Exposure to titanium and nickel as the novel risk factors for PCOS: Evidence from a case control study in Xiamen, China - Zhineng Fu; Lanlan Liu; Jingyi Wang; Fengkai Ruan; Yurong Chen; Liying Zhou; Chunyan Yang; Jiali Cai; Runzeng Liu; Chengyong He; Xiaoming Jiang; Zhenghong Zuo (Journal of Environmental Sciences, 2026)

Lignin–polyether-based abamectin nanospheres for efficient utilization and biological safety - Yurong Chen; Xuexian Wang; Yong Qian; Dongjie Yang; Yuxia Pang; Mingsong Zhou (Chemical Engineering Journal, 2026)

A major qualitative trait locus increases antioxidant activity in testaless peanut seeds - Xing Zhao; Yurong Li; Xiaodong Tang; Sijie Liu; Qiao Su; Pengju Hu; Xinxin Jin; Yahui Song; Jin Wang; Yongqing Yang (Theoretical and Applied Genetics, 2026)

N6-Methyladenosine-Driven Nuclear Export of circKCNN2 Impairs GRP75 Function to Promote Neuronal Apoptosis - Keping Chen; Xin Zhang; Huidi Sun; Yurong Xu; Chuankun Yang (Molecular Neurobiology, 2026)

SMRT sequencing combined with physicochemical and sensory analysis reveals differences in microbial community structure and quality among medium-high-temperature Daqu samples from Shandong Province - Yurong Wang; Qiangchuan Hou; Chengcong Yang; Xinhe Zhao; Chunhui Xin; Ling Xu; Zhuang Guo (Food Bioscience, 2025)

Synergistic anion-cation redox in a P2/O3 biphasic high-entropy layered oxide - Yurong Wu; Haidi Yang; Mengzhao Zhu; Runguo Zheng; Zhishuang Song; Dan Wang; Yanguo Liu; Zhiyuan Wang (Chemical Engineering Journal, 2025)

ITZO/Ga2O3 heterostructure memristor with integrated optoelectronic synaptic function for neuromorphic vision applications - Yonghui Lin; Lun Zhong; Lu Wang; Yuxuan Nie; Fupeng Yang; Jianyong Pan; Yurong Liu; Ruohe Yao; Yang Li; Kuiwei Geng (Chemical Engineering Journal, 2025)

Construction and validation of the DEM-MBD coupling model of reuleaux triangular chain vibrating potato-soil separation interactions in hilly areas combine harvester - Mingdong Chen; Pengxiang Hu; Hongru Zhu; Guanzheng Shi; Weijiang Zhu; Haifeng Kou; Xinting Zhai; Ronghui Wang; Jiandong Zhou; Yongqing Li; Yurong Yang; Xiaojun Meng; et al. (Computers and Electronics in Agriculture, 2025)

Point discharge molecular emission spectrometer as a highly sensitive GC detector for the analysis of furans in food products - Yuan Yang; Xiaoli Wu; Qiuyi Yan; Hongling Zhou; Yurong Deng; Chengbin Zheng (Food Chemistry, 2025)

Cinnamaldehyde nanoemulsion disrupts Listeria monocytogenes biofilms: Metabolomics reveals dual inhibition and removal mechanisms - Yurong Yang; Huayan Cheng; Qiujin Zhu; Jing Wan (Food Bioscience, 2025)

A novel model for the cumulative plastic strain of saturated clay under long-term cyclic loading based on the Laboratory test - Lu Chen; Chengshun Xu; Ke Liang; Yurong Yang (Marine Georesources & Geotechnology, 2025)

Mechanistic insights into lead uptake and immobilization mediated by soybean biochar and arbuscular mycorrhizal fungi in Bidens parviflora - Sadam Khan; Irfan Ullah Shah Syed; Muhammad Riaz; Muhammad Tariq; Tahir shah; Sidra Sohail; Muhammad Imtiaz; Shoaib Akhtar; Jiang Yuanren; Munib Ahmad; Yurong Yang; Hanzhong Jia (Applied Soil Ecology, 2025)

Isotopic signaling and environmental significance of cave waters in a heavily rocky desertification area - Ju Ni; Yurong Mu; Dayun Zhu; Jialu Wang; Yurong Han; Yingshan Zhao; Ning Yang; Juanfang Du (Applied Geochemistry, 2025)

Biorefinery of a newly isolated Nitzschia sp. from Salt Lake for the sequential production of bioactive substances and photovoltaic anti-reflective coating - Qinyun Xu; Shuonan Cao; Xiao Cheng; Shuaili Huang; Liqin Sun; Yurong Zhu; Xin Liu; Jiaoyu Peng; Keli Yang; Zhongliang Sun; Shikai Wang (Algal Research, 2025)

Voltage-induced biomass carbon reconstruction: Creating bifunctional Cu single-atom catalysts for efficient acidic OER and NO₃RR - Mengyi Xu; Shuna Yang; Linqin Wang; Hui Xu; Wenqi Liu; Yurong Su; Yanjie Huang; Ziyi Wang; LiXia Wang; Xianfu Zheng; Yuchen Qin; Feng Huo; et al. (Chemical Engineering Journal, 2025)

Impacts of Biochar and Controlled-Release Urea Co-Application on Soil Bacteria Community and Maize-Wheat Yield in a 3-Year Field Trial - Xiyu Xiang; Huiying Zhao; Mengya Yang; Jiahui Chen; Haiyang Zhang; Shuchen Sun; Sheng Zhai; Yurong Chen; Xiaofei Tian (Journal of Soil Science and Plant Nutrition, 2025)

Rhubarb with Different Cooking Methods Restored the Gut Microbiota Dysbiosis and SCFAs in Ischemic Stroke Mice - Jing Xu; Taotao Liu; Fuzhu Pan; Xuan Ao; Lan Wang; Rixin Liang; Yuxin Lei; Yurong Ding; Miao Yu; Li Li; Hongjun Yang (Molecular Neurobiology, 2025)

Phenological shifts drive rhizosphere microbial community dynamics in Subtropical woody bamboo (Chimonobambusa utilis (Keng) P. C. Keng): pH and total phosphorus as main drivers - Zhiming Zhang; Yurong Cao; Maosheng Sun; Lianchun Wang; Hanqi Yang (Rhizosphere, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Heat rectification effect enables all-season thermal management-electricity cogeneration using dual-mode metawood bricks with aligned semi-pores design - Xiaodan Wu; Jing Liu; Siying Guo; Xin Zhao; Yunjie Yang; Yurong Pan; Fulin Cheng; Yi Chen; Yibo Wang; Zechang Wei; Chenyang Cai; Wenbo Chen (Chemical Engineering Journal, 2025)

Rapid Identification of Soybean SC15 Resistance Locus to Soybean Mosaic Virus by BSA-seq - Xiangmin Tang; Gang Jin; Huaizhu Chen; Zhaoyan Cai; Zhenguang Lai; Qingyuan Wei; Kai Li; Haijian Zhi; Yurong Tan; Dongliang Chen; Weiying Zeng; Shouzhen Yang (Plant Molecular Biology Reporter, 2025)

Remote effect of tropical South Atlantic variability on the Pacific–Japan pattern - Wenwen Yang; Xichen Li; Lin Wang; Yurong Hou; Yonghao Wang; Yujie Miao; Weihan Ma (Climate Dynamics, 2025)

Improvement of near-infrared spectroscopic assessment methods for the quality of Keemun black tea: Utilizing transfer learning - Yurong Chen; Junhan Wang; Jingfei Shen; Yifan Zuo; Qianfeng Yang; Yongning Wei; Jichen Wang; Qing Yu; Wenjun Lv; Luqing Li (Food Research International, 2025)

Micron-engineered phosphorus-rich biochar: A strategy for mitigating metalloid mobility, enhancing bacterial biomass, and improving rice (Oryza sativa L.) quality in antimony mining regions - Hanbo Chen; Jianhong Li; Meng Li; Jiayi Li; Ajit K Sarmah; Xiaokai Zhang; Yurong Gao; Zheng Fang; Xing Yang; Yuxue Liu; Chongjun Chen; Shengdao Shan; et al. (Chemical Engineering Journal, 2025)

Thermal environment control units for multi-objective urban optimization in territorial spatial planning - Genyu Xu; Huihui Zhao; Jinglei Li; Chengfang Wang; Yurong Shi; Lingye Yao; Yaoning Yang; Jian Xu; Ruiqu Ma (Sustainable Cities and Society, 2025)

Why do rice farmers reuse pesticides after purchasing regional pest control services? - Lin Tang; Xiaofeng Luo; Sanxia Du; Yanzhong Huang; Yurong Yang (Environment, Development and Sustainability, 2025)

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

Pig manure biochar in soil forms catalytic system with endogenous H2O2 to degrade ciprofloxacin in purple soil - Guo Chen; Jing Ma; Qian Cai; Jun Wu; Min Xu; Gang Yang; Lulu Long; Chao Chen; Yurong Huang; Ziyu Tian (Chemical Engineering Journal, 2024)

3D printed microplasma optical emission spectrometry coupled with ZIF-8 based dispersive solid-phase extraction for field analysis of waterborne arsenic - Jiahui Yang; Yao Lin; Xi Wang; Yuanyuan Li; Yurong Deng; Chengbin Zheng (Analytica Chimica Acta, 2024)

Seismogenic Structure and Stress State Associated with the 2023 Jishishan Earthquake, NE Tibetan Plateau - Yihai Yang; Qian Hua; Xuemei Zhang; Xiaofei Han; Chong Cao; Yurong Qiu (Pure and Applied Geophysics, 2024)

Deciphering microbial drivers of soil organic matter mineralization in surface and subsurface soil during long-term vegetation succession - Jingwei Shi; Lei Deng; Lin Yang; Yajing Dong; Yang Liao; Jiwei Li; Yurong Liu; Chengjie Ren; Feng Yang; Zhouping Shangguan; Yakov Kuzyakov (Agriculture, Ecosystems & Environment, 2024)

Inflammatory biomarkers mediate the association between polycyclic aromatic hydrocarbon exposure and dyslipidemia: A national population-based study - Jiaqi Chen; Yurong Zhang; Ruijie Wu; Zilin Li; Tongchao Zhang; Xiaorong Yang; Ming Lu (Chemosphere, 2024)

Dielectric barrier discharge-induced chemical vapor generation for highly sensitive analysis of iodine in seawater by ICP-MS - Yuke Wu; Jiahui Yang; Yurong Deng; Jinyi Zhang; Chengbin Zheng (Analytica Chimica Acta, 2024)

Apoptosis and pyroptosis in the nasal mucosa of Syrian hamster during SARS-CoV-2 infection and reinfection - Heng Li; Xin Zhao; Xinglong Zhang; Huiwen Zheng; Yibin Wang; Jinghan Hou; Jing Li; Yurong Zhao; Shasha Peng; Yingyan Li; Xin Zhang; Yifan Zhang; et al. (Apoptosis, 2024)

Does the popularization of ICT promote rural toilet retrofitting?: Micro evidence from a survey of farmer households in 5 Chinese provinces - Zhaoliang Li; Xin Zheng; Yurong Yang (Environment, Development and Sustainability, 2024)

QTL mapping of downy mildew resistance in foxtail millet by SLAF‑seq and BSR-seq analysis - Xu Liu; Nuo Zhang; Yurong Sun; Zhenxin Fu; Yuanhuai Han; Yang Yang; Jichun Jia; Siyu Hou; Baojun Zhang (Theoretical and Applied Genetics, 2024)

Per- and polyfluoroalkyl substances (PFASs) in bivalve molluscs from Shandong Province, China: Occurrence, distribution, and implications for human consumption - Lijun Zhu; Yanni Jiao; Liyou Wang; Peirui Xiao; Xiaoyang Li; Zhendong Yin; Tianliang Zhang; Wenbin Zhu; Yurong Liu; Jiacheng Zhang; Luping Yang (Marine Pollution Bulletin, 2024)

Methods for quantification of biochar in soils: A critical review - Yanhai Xie; Caibin Li; Hanbo Chen; Yurong Gao; Tony Vancov; Brad Keen; Lukas Van Zwieten; Yunying Fang; Xiwen Sun; Yi He; Xiaofei Li; Nanthi Bolan; et al. (CATENA, 2024)

Arsenic field test kits based on solid-phase fluorescence filter effect induced by silver nanoparticle formation - Wenhui Yang; Liqing Ye; Yuke Wu; Xi Wang; Simin Ye; Yurong Deng; Ke Huang; Hong Luo; Jinyi Zhang; Chengbin Zheng (Journal of Hazardous Materials, 2024)

Pristine and Fe-functionalized biochar for the simultaneous immobilization of arsenic and antimony in a contaminated mining soil - Jiayi Li; Yurong Gao; Caibin Li; Fenglin Wang; Hanbo Chen; Xing Yang; Paramsothy Jeyakumar; Binoy Sarkar; Zhenbao Luo; Nanthi Bolan; Xiaofei Li; Jun Meng; et al. (Journal of Hazardous Materials, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Investigating the electron-scale adsorption mechanisms using DFT calculations and experimental studies in self-assembly magnetic biochar gel incorporated with graphene nanosheets for enhanced Sb(III) removal - Hanbo Chen; Yurong Gao; Zheng Fang; Jiayi Li; Suresh C. Pillai; Hocheol Song; Chenghua Sun; Nanthi Bolan; Xing Yang; Meththika Vithanage; Shengdao Shan; Hailong Wang (Chemical Engineering Journal, 2024)

The Effects of Dietary Fermented Soybean Residue on the Growth, Antioxidant Capacity, Digestive Enzyme Activities, and Microbial Compositions of the Intestine in Furong Crucian Carp (Furong Carp♀ × Red Crucian Carp♂) - Hongquan Wang; Zheming Zhang; Feilong Li; Liang Hu; Tiaoyi Xiao; Yurong Zhao; Mengxi Yang (Fishes, 2024)
An 8-week feeding experiment aimed to investigate the effects of fermented soybean residue in diets on the growth performance, serum antioxidant parameters, intestinal digestive capacity, and microbial composition of the hindgut of Furong crucian carp. The feeds were formulated to contain 0%, 6%, 12%, 18%, and 24% fermented soybean residue (CON, FSR6, FSR12, FSR18, and FSR24, respectively), respectively, to form five diets (crude protein: 33%; crude lipid: 5%). The results showed that incorporating 6% fermented soybean residue into the diet significantly increased the weight gain rate (WGR) and specific growth rate (SGR) and decreased the feed coefficient rate (p

Fabrication of hyaluronic acid-altered gold complex delivery for head and neck squamous cell carcinoma therapy with high antitumor efficacy and low in vivo toxicity - Shizhi He; Jiaming Chen; Yanming Zhao; Ru Wang; Yurong He; Shaoshi Chen; Yifan Yang; Changyu Zhu; Jingyang Zhao; Jugao Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Asymmetric disturbance and permeabilization of bilayer membranes by 3-nm carbon dots - Wenwen Li; Yurong Ma; Luping Ou; Cheng Xu; Yushuang Wei; Kai Yang; Bing Yuan (Journal of Hazardous Materials, 2024)

Achieving high-rate and long-life Zn metal anodes via constructing interfacial gradient heterostructure - Yilun Ren; Biao Wang; Shaozhong Chang; Hao Wu; Yujie Ma; Fengqi Li; Cong Wang; Jian Gu; Yurong Yang; Shaochun Tang; Xiangkang Meng (Chemical Engineering Journal, 2024)

Building a Predictive PBPK Model for Human OATP Substrates: a Strategic Framework for Early Evaluation of Clinical Pharmacokinetic Variations Using Pitavastatin as an Example - Xiaomin Liang; Megan L. Koleske; Jesse Yang; Yurong Lai (The AAPS Journal, 2024)

CLANET: a cross-linear attention network for semantic segmentation of urban scenes remote sensing images - Chao Chen; Yurong Qian; Hui Liu; Guangqi Yang (International Journal of Remote Sensing, 2023)

Gut microbial communities and their potential roles in cellulose digestion and thermal adaptation of earthworms - Yurong Yang; Mac A. Callaham; Xuefeng Wu; Yufeng Zhang; Donghui Wu; Deli Wang (Science of The Total Environment, 2023)

Highly efficient photo-driven generation and elimination of reactive oxygen species in biological environment by gold nanoclusters - Zenan Li; Tianyang Zhang; Jian Shen; Yurong Ma; Kai Yu; Jiacheng Li; Hui Huang; Yang Liu; Zhenhui Kang (Journal of Environmental Chemical Engineering, 2023)

Source–specific probabilistic risk evaluation of potentially toxic metal(loid)s in fine dust of college campuses based on positive matrix factorization and Monte Carlo simulation - Xinwei Lu; Zhenze Wang; Yurong Chen; Yufan Yang; Xinyao Fan; Lingqing Wang; Bo Yu; Kai Lei; Ling Zuo; Peng Fan; Tao Liang; Jin Woo Cho; et al. (Journal of Environmental Management, 2023)

Coupled sorptive and oxidative antimony(III) removal by iron-modified biochar: Mechanisms of electron-donating capacity and reactive Fe species - Yurong Gao; Hanbo Chen; Zheng Fang; Nabeel Khan Niazi; Kwasi Adusei-Fosu; Jianhong Li; Xing Yang; Zhongzhen Liu; Nanthi S. Bolan; Bin Gao; Deyi Hou; Chenghua Sun; et al. (Environmental Pollution, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

An improved wavelet threshold for correcting static effects of MT - Zhijie Zhang; Yunqiu Yang; Yurong Gong (Journal of Applied Geophysics, 2023)

Effects of anthropogenic emissions and meteorological conditions on diurnal variation of formaldehyde (HCHO) in the Yangtze River Delta, China - Yurong Gao; Hao Pan; Le Cao; Chunsong Lu; Qingjian Yang; Xichang Lu; Hongyi Ding; Simeng Li; Tianliang Zhao (Atmospheric Pollution Research, 2023)

Natural resources extraction and sustainable environment: COP26 perspective for China - Yurong Cai; Pengfei Zhou; Yiting Zhang; Yang Shen (Resources Policy, 2023)

Genetic analysis and exploration of major effect QTLs underlying oil content in peanut - Yongqing Yang; Yurong Li; Zengshu Cheng; Qiao Su; Xinxin Jin; Yahui Song; Jin Wang (Theoretical and Applied Genetics, 2023)

Accumulation, transportation, and distribution of tetracycline and cadmium in rice - Chunfeng He; Jini Zhou; Chen Yang; Zhiyi Song; Junheng He; Ziqing Huang; Yurong Deng; Jinling Wang; Yu Xiong; Zhi Dang (Journal of Environmental Sciences, 2023)

How arbuscular mycorrhizal fungi drives herbaceous plants' C: N: P stoichiometry? A meta-analysis - Xin Yang; Yurong Ma; Jianjun Zhang; Haotian Bai; Yue Shen (Science of The Total Environment, 2023)

Physical modification on gelation of fish gelatin by incorporating Nicandra physalodes (Linn.) Gaertn. pectin: Effect of monovalent and divalent cation ions - Kai Yuan; Shuai Luo; Huan Zhang; Xudong Yang; Shuai Zhang; Xi Yang; Yurong Guo (Food Chemistry, 2023)

Regulation on gel textures of Nicandra physalodes (Linn.) Gaertn. pectin by its synergistic interaction with sodium alginate - Xudong Yang; Kai Yuan; Huan Zhang; Shuai Luo; Shuaida Wang; Xi Yang; Yurong Guo (Food Hydrocolloids, 2023)

Effects of long-term ambient air pollution exposure on township-level pulmonary tuberculosis notification rates during 2005–2017 in Ningxia, China - Igor Popovic; Ricardo J. Soares Magalhães; Yurong Yang; Shukun Yang; Boyi Yang; Guanghui Dong; Xiaolin Wei; Greg J. Fox; Melanie S. Hammer; Randall V. Martin; Aaron van Donkelaar; Erjia Ge; et al. (Environmental Pollution, 2023)

Micron SiOx encapsulated into amorphous B, N Co-doped carbon nanotube network for high-capacity and long-durable Li-ion half/full batteries - Bingxin Shen; Ning Fu; Yuwen Chen; Wei Shao; Yurong Yan; Jia Huang; Zhenglong Yang (Chemical Engineering Journal, 2023)

Boosting solar-powered interfacial water evaporation by architecting 3D interconnected polymetric network in CNT cellular structure - Liming Zhao; Zhengpeng Yang; Jiaojiao Wang; Yurong Zhou; Pei Cao; Jian Zhang; Peng Yuan; Yongyi Zhang; Qingwen Li (Chemical Engineering Journal, 2023)

Evaluation of the coordination between marine ecological environment protection and marine economic development in China - Ling Cai; Junlang Liang; Zhouhua Guo; Yurong Ouyang; Ming Yang; Juanjuan Dai (Environmental Science and Pollution Research, 2022)

Seasonal Variation of Catenary-Bead Dunes in the Yangtze River Estuary: Causes and Implications - Shuwei Zheng; Xinmeng Yuan; Suxian Yang; Heqin Cheng; Xingjie Guo; Yurong Cui; Enfeng Liu; Zijun Li (Journal of Marine Science and Engineering, 2022)
Low-angle lee-side slopes of dunes are commonly developed on the world’s riverbeds, and dune migration associated with sediment transport exert a major influence on riverine processes. However, the catenary-bead dune has been identified in the Yangtze River (YR) Estuary, featuring a higher lee-side angle. To date, the morphological variation and formation reasons of catenary-bead dunes in the YR Estuary remain uncharacterized. In this study, we used a multibeam echo system (MBES) to investigate the bedforms of the YR estuary during 2014–2015, as well as to discuss the seasonal variation of catenary-bead dunes. The results indicate that the catenary-bead dunes of the YR Estuary are characterized by growth during the flood season and extinction during the dry season. The lee-side angle is typically ~16.7°, which is larger than that of other dune types (3.7–8°) in the estuary; moreover, the catenary-bead dunes are higher than other dune types of the same length in the YR Estuary. The relationship between the dune height (H) and length (L) was found to be H = 0.1667L0.603 (R2 = 0.38), while the other dune types yielded the relationship of H = 0.0845L0.758 (R2 = 0.52). Strong runoff superimposing the ebb tide led to the development of catenary-bead dunes. Furthermore, the higher coarse sediment content (69.9–72%) and lower clay content (6.3–6.7%) of the riverbed sediment are favorable for their formation, while the higher curved crest-lines are favorable for the formation of the associated elliptical pits.

Rapid and specific detection of Fusarium acuminatum and Fusarium solani associated with root rot on Astragalus membranaceus using loop-mediated isothermal amplification (LAMP) - Yan Wang; Chunwei Wang; Yurong Ma; Xiqian Zhang; Hongbin Yang; Guangxin Li; Xinfeng Li; Meiqin Wang; Xiaojun Zhao; Jianming Wang; Xianhong Zhang (European Journal of Plant Pathology, 2022)

Heavy metal domestication enhances beneficial effects of arbuscular mycorrhizal fungi on lead (Pb) phytoremediation efficiency of Bidens parviflora through improving plant growth and root Pb accumulation - Yurong Yang; Beitong Huang; Jiazheng Xu; Zhenxin Li; Zhanhui Tang; Xuefeng Wu (Environmental Science and Pollution Research, 2022)

Association between serum folate levels and blood concentrations of cadmium and lead in US adults - Zuxiang Wu; Huan Hu; Chenxi Wang; Ji Wu; Yurong Xiong; Yang Fu; Xiaoshu Cheng; Hai Su; Ping Li (Environmental Science and Pollution Research, 2022)

Pathogenicity of Salmonella During Schistosoma-Salmonella Co-infections and the Importance of the Gut Microbiota - Ousman Bajinka; Mingming Qi; Amadou Barrow; Abdoulie O. Touray; Lulu Yang; Yurong Tan (Current Microbiology, 2022)

A study on water quality prediction by a hybrid CNN-LSTM model with attention mechanism - Yurong Yang; Qingyu Xiong; Chao Wu; Qinghong Zou; Yang Yu; Hualing Yi; Min Gao (Environmental Science and Pollution Research, 2021)

Bacillus megaterium strain WW1211 promotes plant growth and lateral root initiation via regulation of auxin biosynthesis and redistribution - Shengwang Wang; Xiaofan Na; Lei Yang; Cuifang Liang; Li He; Jie Jin; Ziyu Liu; Juan Qin; Junjie Li; Xiaomin Wang; Yurong Bi (Plant and Soil, 2021)

miR-146a-3p suppressed the differentiation of hAMSCs into Schwann cells via inhibiting the expression of ERBB2 - Wei Chen; Linlin Ji; Zairong Wei; Chenglan Yang; Shusen Chang; Yucheng Zhang; Kaiyu Nie; Lingli Jiang; Yurong Deng (Cell and Tissue Research, 2021)
Human amniotic mesenchymal stem cells (hAMSCs) can be differentiated into Schwann-cell-like cells (SCLCs) in vitro. However, the underlying mechanism of cell differentiation remains unclear. In this study, we explored the phenotype and multipotency of hAMSCs, which were differentiated into SCLCs, and the expression of nerve repair-related Schwann markers, such as S100 calcium binding protein B (S-100), TNF receptor superfamily member 1B (P75), and glial fibrillary acidic protein (GFAP) were observed to be significantly increased. The secreted functional neurotrophic factors, like brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), and neurotrophin-3 (NT-3), were determined and also increased with the differentiation time. Moreover, miR-146a-3p, which significantly decreased during the differentiation of hAMSCs into SCLCs, was selected by miRNA-sequence analysis. Further molecular mechanism studies showed that Erb-B2 receptor tyrosine kinase 2 (ERBB2) was an effective target of miR-146a-3p and that miR-146a-3p down-regulated ERBB2 expression by binding to the 3′-UTR of ERBB2. The expression of miR-146a-3p markedly decreased, while the mRNA levels of ERBB2 increased with the differentiation time. The results showed that down-regulating miR-146a-3p could promote SC lineage differentiation and suggested that miR-146a-3p negatively regulated the Schwann-like phenotype differentiation of hAMSCs by targeting ERBB2. The results will be helpful to establish a deeper understanding of the underlying mechanisms and find novel strategies for cell therapy.

miR-29a is a negative regulator of influenza virus infection through targeting of the frizzled 5 receptor - Xiaoyun Yang; Yurong Liang; Gayan Bamunuarachchi; Yanzhao Xu; Kishore Vaddadi; Samuel Pushparaj; Dao Xu; Zhengyu Zhu; Rachel Blaha; Chaoqun Huang; Lin Liu (Archives of Virology, 2021)

Genetic diversity analysis of intraspecific hybridization between Plumbago auriculata and Plumbago auriculata f. alba based on horticultural traits and molecular markers - Xi Chen; Suping Gao; Ping Shen; Yingqi Liu; Ting Lei; Lisha Shi; Wenji Li; Yurong Li; Xiaofang Yu; Lijuan Yang; Jiani Li (Acta Physiologiae Plantarum, 2021)

Heat-air-moisture coupled model for radon migration in a porous media - Yu Cui; Shengyang Feng; Puxin Chen; Yongjun Ye; Yurong Wu; Ce Li; Rong Yang; Hong Wang (Environmental Science and Pollution Research, 2020)

Involvement of active MKK9-MAPK3/MAPK6 in increasing respiration in salt-treated Arabidopsis callus - Jie Liu; Xiaomin Wang; Lei Yang; Wenbin Nan; Mengjiao Ruan; Yurong Bi (Protoplasma, 2020)

Social capital and the use of organic fertilizer: an empirical analysis of Hubei Province in China - Yurong Yang; Yucheng He; Zhaoliang Li (Environmental Science and Pollution Research, 2020)

High-throughput Sequencing-based Analysis of Microbial Diversity in Rice Wine Koji from Different Areas - Xinxin Zhao; Yurong Wang; Wenchao Cai; Mingjun Yang; Xiaodan Zhong; Zhuang Guo; Chunhui Shan (Current Microbiology, 2020)

Interactive effects of exogenous melatonin and Rhizophagus intraradices on saline-alkaline stress tolerance in Leymus chinensis - Yurong Yang; Yaping Cao; Zhenxin Li; Anastasiia Zhukova; Songtao Yang; Jinlong Wang; Zhanhui Tang; Yonghong Cao; Yifei Zhang; Deli Wang (Mycorrhiza, 2020)

Nitric oxide and hydrogen peroxide increase glucose-6-phosphate dehydrogenase activities and expression upon drought stress in soybean roots - Xiaomin Wang; Mengjiao Ruan; Qi Wan; Wenliang He; Lei Yang; Xinyuan Liu; Li He; Lili Yan; Yurong Bi (Plant Cell Reports, 2020)

Interactions Between Different Selenium Compounds and Essential Trace Elements Involved in the Antioxidant System of Laying Hens - Xue Lin; Ting Yang; Hua Li; Yinli Ji; Yurong Zhao; Jianhua He (Biological Trace Element Research, 2020)

Effects of oral florfenicol on intestinal structure, function and microbiota in mice - Shiyu Yun; Yurong Guo; Lan Yang; Xin Zhang; Weiqi Shen; Zhuo Wang; Shuang Wen; Dongdong Zhao; Haiping Wu; Jia Chen; Yaogui Sun; Zhibian Duan (Archives of Microbiology, 2020)

Unbiased groupwise registration for shape prediction of foot scans - Jianjun Zhu; Xiuxing Wang; Shaodong Ma; Jingfan Fan; Shuang Song; Xiao Ma; Danni Ai; Hong Song; Yurong Jiang; Yongtian Wang; Jian Yang (Medical & Biological Engineering & Computing, 2019)

Identification and mapping of a photoperiod response gene (QPpd.zafu-4A) on wild emmer wheat (Triticum turgidum L.) chromosome 4AL - Jinsheng Yu; Yunzheng Miao; Siqing Yang; Zhaobin Shi; Nana Miao; Mingquan Ding; Hua Zhang; Yurong Jiang; Junkang Rong (Euphytica, 2019)

Alternative respiration pathway is involved in the response of highland barley to salt stress - Qiang He; Xiaomin Wang; Li He; Lei Yang; Shengwang Wang; Yurong Bi (Plant Cell Reports, 2019)

A genetic system on chromosome arm 1BL of wild emmer causes distorted segregation in common wheat - Yunzheng Miao; Siqing Yang; Yurong Jiang; Junkang Rong; Jinsheng Yu (Journal of Genetics, 2018)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Transcriptomic analysis of the effects of three different light treatments on the biosynthesis of characteristic compounds in the tea plant by RNA-Seq - Xinyuan Hao; Litian Li; Yurong Hu; Chao Zhou; Xinchao Wang; Lu Wang; Jianming Zeng; Yajun Yang (Tree Genetics & Genomes, 2016)

Narciclasine, a potential allelochemical, affects subcellular trafficking of auxin transporter proteins and actin cytoskeleton dynamics in Arabidopsis roots - Yanfeng Hu; Xiaofan Na; Jiaolong Li; Lijing Yang; Jia You; Xiaolei Liang; Jianfeng Wang; Liang Peng; Yurong Bi (Planta, 2015)

Genetic fine mapping and candidate gene analysis of the Gossypium hirsutum Ligon lintless-1 (Li1) mutant on chromosome 22(D) - Yurong Jiang; Mingquan Ding; Yuefen Cao; Fen Yang; Hua Zhang; Shae He; Huaqin Dai; Huanfeng Hao; Junkang Rong (Molecular Genetics and Genomics, 2015)

Life cycle environmental impact assessment of a bridge with different strengthening schemes - Bo Pang; Pengchao Yang; Yuanfeng Wang; Alissa Kendall; Huibing Xie; Yurong Zhang (The International Journal of Life Cycle Assessment, 2015)

Assessment of arbuscular mycorrhizal fungi status and heavy metal accumulation characteristics of tree species in a lead–zinc mine area: potential applications for phytoremediation - Yurong Yang; Yan Liang; Amit Ghosh; Yingying Song; Hui Chen; Ming Tang (Environmental Science and Pollution Research, 2015)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Inhibition of root growth by narciclasine is caused by DNA damage-induced cell cycle arrest in lettuce seedlings - Yanfeng Hu; Jiaolong Li; Lijing Yang; Wenbin Nan; Xiaoping Cao; Yurong Bi (Protoplasma, 2014)

Arbuscular Mycorrhizal Fungi Alter Fractal Dimension Characteristics of Robinia pseudoacacia L. Seedlings Through Regulating Plant Growth, Leaf Water Status, Photosynthesis, and Nutrient Concentration Under Drought Stress - Yurong Yang; Ming Tang; Ronan Sulpice; Hui Chen; Shuai Tian; Yihui Ban (Journal of Plant Growth Regulation, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Real-time quantitative analysis of the influence of blue light on citrinin biosynthetic gene cluster expression in Monascus - Changlu Wang; Hua Yang; Mianhua Chen; Yurong Wang; Fengjuan Li; Cheng Luo; Shuyi Zhao; Dong He (Biotechnology Letters, 2012)

Narciclasine inhibits the responses of Arabidopsis roots to auxin - Yanfeng Hu; Lijing Yang; Xiaofan Na; Jia You; Wei Hu; Xiaolei Liang; Jie Liu; Lina Mao; Xiaoming Wang; Huahua Wang; Yurong Bi (Planta, 2012)

Comparison of landscape patterns between metropolises and small-sized cities: a gradient analysis with changing grain size in Shanghai and Zhangjiagang, China - Qi Yang; Jianlong Li; Xiaoyu Gan; Jie Zhang; Feng Yang; Yurong Qian (International Journal of Remote Sensing, 2012)

Expressing and characterization of mlin-41 in mouse early embryos and adult muscle tissues - Gang Yu; Yurong Yang; Guimei Tian (Journal of Molecular Histology, 2010)

Reversal of Osteoporotic Changes of Mineral Composition in Femurs of Diabetic Rats by Insulin - Xiaolin Zhang; Yurong Fei; Min Zhang; Dan Wei; Ming Li; Wenjun Ding; Jianhong Yang (Biological Trace Element Research, 2008)